E-learning readiness and perceived stress among the university students of Bangladesh during COVID-19: a countrywide cross-sectional study. (1st January 2021) - Kabir, Humayun; Hasan, Md. Kamrul; Mitra, Dipak Kumar
Abstract: Background: The COVID-19 pandemic has compelled all educational institutions from the conventional campus-based education system to e-learning worldwide. However, adapting to this new platform, e-learning readiness may cause perceived stress among students. This study aimed to examine the association between e-learning readiness and perceived e-learning stress and the relationship between sociodemographic and e-learning related factors. Results: A cross-sectional study was employed, where 1145 e-learning enrolled university students were surveyed. The result indicated that nearly 91% of students reported moderate (76.07%) to the higher level (14.85%) of perceived e-learning stress, whereas more than half of them (58.17%) were at the sub-optimum level of readiness. Furthermore, it was found that students with the sub-optimum level of readiness compared to optimum had a significantly higher chance of reporting moderate and high level of perceived e-learning stress. Besides, parents' highest education, residence, students' preference in (e-learning or learning format), and having any eye problems were associated with perceived e-learning stress. Conclusions: A sudden introduction of e-learning during the COVID-19 catastrophe has brought about challenges, including the students' readiness, that might exacerbate the perceived stress level in different ways. This study reported that most of the students were at sub-optimal levels of readiness and suffered from moderate to high levels of perceived e-learning stress. The findings should integrate into the education monitoring system to enhance students' coping strategies, incite readiness, straighten, and nourish existing policies. Key messages: The moderate and higher level of e-learning stress was 76% and 15%, respectively. Here, 58% of students were at the sub-optimum level of e-learning readiness. Students' sub-optimum level of e-learning readiness was significantly associated with the perceived moderate and high level of e-learning stress.